Effect of the Alkyl Chain Length Incorporated into Donor Part on the Optoelectronic Properties of the Carbazole Based Dyes: Theoretical Study - Souad El Mzioui; Si Mohamed Bouzzine; Mohammed Bouachrine; Mohamed Naciri Bennani; Mohamed Hamidi (Orbital: The Electronic Journal of Chemistry, 2017)
In this paper, we report a theoretical study using density functional theory (DFT) and time-dependent (TD-DFT) for R-D-π-A systems with various alkyl chains (R). Results show that the LUMO of the dye lies above the semiconductor conduction band, promoting the injection of electrons; the lower HOMO level promotes dye regeneration. The incorporation of methyl chain (CH3) has a significant reduction in the gap energy, improved red-shift absorption spectrum and increase the molar extinction coefficient at the maximum absorption wavelength compared to D. While, the increase in alkyl chain length from C2H5 to C6H13 present a relatively reduce of gap energies, low effect on the wavelength (438 nm) and converged excitation energies.DOI: http://dx.doi.org/10.17807/orbital.v9i5.1003